Comparing some the Tripartite Consequences of Leisure-Recreational Sports among Selected University Students in Iran and Iraq - haitham gaze Ahmed; Farzam Farzan; Vahid Saatchian (دراسات وبحوث التربية الرياضية)
The purpose of this study was to compare the triple consequences of recreational sports among selected Iranian and Iraqi university students.  and then thematic analysis was used to analyze the data. In the quantitative part, the Kendall W and independent t-tests were used. Based on the findings of the qualitative part, out of a total of 202 identified basic themes, 43 themes constituted physical outcomes, including the development of individual skills and abilities, reduction of injuries and illnesses, physical vitality, and contribution to the proper functioning of body organs; 75 themes constituted psycho-emotional outcomes, including individual growth, moral-behavioral development, emotional-trait development, and life development; and 84 themes constituted social outcomes, including social growth, communication development, improvement of social status, and social life development. In the quantitative part, it was also found that there is a significant priority between the triple consequences of recreational sports from the perspective of Iraqi and Iranian students, so that "psycho-emotional outcomes" from the perspective of Iraqi students and "physical outcomes" from the perspective of Iranian students were the first priority. Also, it was found that there is a significant difference between the triple consequences in the two groups of students, and this difference in all cases is higher in favor of Iraqi students.